TEMPO RATING APPROACH USING FUZZY RULE BASED SYSTEM AND WESTINGHOUSE METHOD FOR THE ASSESSMENT OF NORMAL TIME - (:unkn) unknown (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2016)
Tempo rating which aims to obtain the accurate tempo for the workers is an important process for time study applications. It is possible to reach the normal time after finding the precise tempo values. Westinghouse method, based on the factors of skill, effort, environmental conditions and consistency, can be considered as one of the well-known methods among tempo rating approaches. However, crisp numerical values with linguistic terms are used for evaluating each factor in Westinghouse method. In this study, a fuzzy rule based methodology is proposed due to the vague environment of decision making process of tempo rating. The developed methodology includes fuzzy rules for determining the evaluation scores of each factor. The proposed rating system is applied in a bus-bar production system so as to demonstrate its validity. The proposed rating system yields high level of conciseness on the basis of predetermined motion time system. Significance: Since time study activities are performed in all the industries including every sector, tempo rating which is critical for finding the normal time of the tasks is very important and has a wide range of industrial applications. With this study, a new tempo rating methodology based on fuzzy rule based system is presented. The proposed methodology provides easiness to use and produces accurate values.
Keywords: time study; tempo (performance) rating; westinghouse method; fuzzy rule based system; WORK MEASUREMENT; INDUSTRY; MOTION; CLASSIFICATION; MODEL